Stable, high-performance vertical heterojunction ultraviolet photodetectors with Ga2O3-protected Ag nanowires window electrode - Xingyuan Yu; Yujie Peng; Di Zhang; Fuqiang Zhai; Hua Tang; Jiang Cheng; Lu Li; Xin Yang; Feng Cheng (ChemPhysMater)
Large-scale ultraviolet photodetectors are highly promising for detection of weak signals and have the potential for widespread applications in high-tech areas such as aerospace detection and wearable devices. However, the commonly used window electrodes lack transparency to ultraviolet light. Although ultraviolet photodetectors based on Ag nanowires exhibit good response due to their broad transparency range, the sharp interface between the Ag nanowires and the semiconductor renders them extremely unstable. Surface protection is considered to enhance the stability and lifespan of these devices. Our research has revealed that amorphous Ga2O3 can fully encapsulate the surface of Ag nanowires and securely affix it to the NiO film, resulting in a stable performance with a high responsivity of 48 mA W−1 and detectivity of 6.1 × 1011 Jones for 254 nm light. The unpacked device exhibited a stable photocurrent, showing only 6.8% degradation after 3 months in ambient air. Finally, a large-scale (5 cm × 4 cm, with 12 cm2 of active area) ultraviolet photodetector with a Ga2O3-protected Ag nanowire electrode was prepared, which demonstrated a milliamp-level photocurrent under weak ultraviolet illumination that can be directly read by a conventional multimeter in practical scenarios, indicating the promising prospects of this device for future commercial applications.